Prussian Blue nanoparticles supported on a hybrid platform of graphene oxide and cubic silsesquioxane applied to Diuron detection - Maraldi, Vitor Alexandre [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Elsevier, 2023)
This work describes the preparation and chemical modification of the graphene oxide platform with octa(aminopropyl)silsesquioxane, with subsequent deposition of Prussian Blue nanoparticles on its surface. The materials were characterized by Raman Spectroscopy, X-Ray Excited Photoelectron Spectroscopy and Transmission Electron Microscopy, which ensured the success of the proposed synthesis. The Differential Pulse Voltammetry technique was employed in order to apply the conventional electrode as a sensor for the detection of Diuron, a widely used pesticide due to its efficiency in controlling a wide range of weeds and grasses, but which has carcinogenic and genotoxic effects. The graphite paste electrode modified with the metallic complex was electroactive in the electrocatalytic detection of Diuron, with a detection limit of 4.96 nmol·L−1. Given this, it can be proposed that the material prepared in this work is included in the list of potential candidates for the development of electrochemical sensors for the detection of Diuron.
Keywords: A. composites; A. nanostructures; B. chemical synthesis; C. electrochemical measurements; D. electrochemical properties